207: Emergency Department and Inpatient Management of Febrile Infants Under Six-Weeks of Age: Perceived Utility of Respiratory Virus Testing. Issue 6 (1st June 2014) - Burstein, B; Dubrovsky, S; Quach, C
Abstract: BACKGROUND: Well appearing febrile infants with viral illnesses cannot be easily distinguished from those with occult life-threatening infections by history and physical exam alone. This study sought to assess current approaches to febrile infants under six weeks of age, and determine how management is influenced by respiratory virus testing. METHODS: A scenario-based survey describing two hypothetical cases of febrile infants without an infectious focus aged three and five weeks was sent to tertiary care pediatric ED and hospitalist physicians at a single center. Participants were asked multiple-choice questions regarding management decisions with and without results of respiratory virus testing. Chi-square testing was used to compare proportions. RESULTS: Response rate was 93% (n=32 ED, 22 hospitalists). Investigations most commonly performed for both three- and five-week old infants were urine culture, urine analysis, CBC and blood culture. Lumbar puncture was performed less frequently in five-week old infants (69% vs. 98%, P<0.001), and by hospitalists compared to ED physicians (50% vs. 81%, P<0.05). Respiratory virus testing by nasopharyngeal swab (NPA) did not differ between age groups (67% in both), however hospitalists performed NPA testing more frequently than ED physicians (82% vs. 56%, P<0.05). Infant age impacted admission decisions (three- vs. five weeks; 100% vs. 72%, P<0.001), but detection of a respiratory virus did not. Overall, positive NPA decreased empiric antibiotic treatment (P<0.05). Among hospitalists, 82% would discharge five-week old infants in ≤24 h with a positive NPA and otherwise negative workup; whereas admission duration among three-week old infants was highly variable. CONCLUSIONS: The management of febrile infants under six weeks differs between ED and hospitalist physicians, and by infant age. Respiratory virus testing could potentially reduce empirical antimicrobial treatment and permit earlier discharge. Establishment of clinical guidelines for this patient population is warranted.